Implementing evidence-based practices in rural settings: a scoping review of theories, models, and frameworks - Brady, Robert E.; Lyons, Kathleen D.; Stevens, Courtney J.; Godzik, Cassandra M.; Smith, Andrew J.; Bagley, Pamela J.; Vitale, Elaina J.; Bernstein, Steven L. (Frontiers in Health Services, 2024)
BackgroundRural healthcare has unique characteristics that affect the dissemination and implementation of evidence-based interventions. Numerous theories, models, and frameworks have been developed to guide implementation of healthcare interventions, though not specific to rural healthcare. The present scoping review sought to identify the theories, models, and frameworks most frequently applied to rural health and propose an approach to rural health research that harnesses selected constructs from these theories, models, and frameworks. This resulting synthesis can serve as a guide to researchers, policy makers, and clinicians seeking to employ commonly used theories, models, and frameworks to rural health.MethodsWe used the Scopus abstract indexing service to identify peer-reviewed literature citing one or more of theories, models, or frameworks used in dissemination and implementation research and including the word “rural” in the Title, Abstract, or Keywords. We screened the remaining titles and abstracts to ensure articles met additional inclusion criteria. We conducted a full review of the resulting 172 articles to ensure they identified one or more discrete theory, model, or framework applied to research or quality improvement projects. We extracted the theories, models, and frameworks and categorized these as process models, determinant frameworks, classic theories, or evaluation frameworks.ResultsWe retained 61 articles of which 28 used RE-AIM, 11 used Community-Based Participatory Research (CBPR) framework, eight used the Consolidated Framework for Implementation Research (CFIR), and six used the integrated-Promoting Action on Research Implementation in Health Services (iPARIHS). Additional theories, models, and frameworks were cited in three or fewer reports in the literature. The 14 theories, models, and frameworks cited in the literature were categorized as seven process models, four determinant frameworks, one evaluation framework, and one classic theory.ConclusionsThe RE-AIM framework was the most frequently cited framework in the rural health literature, followed by CBPR, CFIR, and iPARIHS. A notable advantage of RE-AIM in rural healthcare settings is the focus on reach as a specified outcome, given the challenges of engaging a geographically diffuse and often isolated population. We present a rationale for combining the strengths of these theories, models, and frameworks to guide a research agenda specific to rural healthcare research.Systematic Review Registrationhttps://osf.io/fn2cd/.